Exakte Partikelgrößen‐ und Formanalyse in einem Messgerät: Kombination statischer Lichtstreuung und dynamischer Bildanalyse. Issue 4 (25th March 2018) - Schleife, Frederik; Klank, Dietmar; Oetzel, Christian
Abstract: Laser diffraction is often used for determination of the particle size distribution. However, besides many advantages of this method, such as short measurement time and wide measurement range, there are also shortcomings. Significant statistical inaccuracies are particularly evident in very broad distributions. For the first time, the particle size distribution of nanometer, micrometer and millimeter particles could be exactly determined with the Bettersizer S3 Plus and individual particle information on the oversize grain and agglomeration phenomena could be obtained. The advantages of combining static light scattering with dynamic image analysis are demonstrated.